A Reversed-phase High Performance Liquid Chromatography (HPLC) method for bio-analysis of Methotrexate - Leila Pourtalebi Jahromi; Soliman Mohammadi-Samani; Hajar Ashrafi; Amir Azadi (Shiraz University of Medical Sciences, 2016)
Methotrexate (MTX) is a chemotherapeutic agent used in treatment of many disorders including autoimmune diseases and cancers. The availability of a reliable analysis method for drug assay in biological fluids of interest  is  a  prerequisite  for  all  pharmacokinetic  studies  in  humans  or  animal  models. Considering the complex matrices of the biological specimens as well as the low concentrations of the majority of the drugs in biological fluids, the development of an available while sensitive method for the bioanalytical studies is often a challenging issue.For drug assay in aqueous, plasma, animal brain and liver tissue environments in a concentration range of 25-600 ng/ml, a reverse phase high performance liquid chromatography (RP-HPLC) was developed.System suitability tests were indicating a method with acceptable analytic separation efficiency and peak shape proving method's selectivity. Limit of detection (LOD) and limit of quantification (LOQ) determined to be 10 ng/ml and 25ng/ml, which reflect method sensitivity. Regression analysis showed a linear correlation between area under curve (AUC) of peaks and corresponding MTX concentrations. The within-day and between-day precision and accuracy was both in acceptable ranges. Recovery index of method for median concentration (200 ng/ml) is also about 74%.The developed method was accorded to the acceptable criteria of analytical method validation. The sensitivity of the method in all the tested matrices made the method suitable in terms of detection and quantitation of low concentration samples throughout the study. Also, the assay method had fairly short run-time and lacks any significant interference.